q-STARLIKE FUNCTIONS OF ORDER ALPHA - (:unkn) unknown (TURKIC WORLD MATHEMATICAL SOC, 2018)
For all q is an element of (0, 1) and 0 <= alpha < 1 we define a class of analytic functions, so-called q-starlike functions of order alpha on the open unit disc D = {z : vertical bar z vertical bar < 1}. We will study this class of functions and explore some inclusion properties with the well-known class Starlike functions of order alpha.
Keywords: q-starlike functions; distortion theorem; growth theorem; coefficient inequality; OPERATORS